Cooperative learning and strategies for inclusion : celebrating diversity in the classroom - 4 0 16; (JoAnne Wachholz), Putnam, JoAnne W.; 5 (Baltimore, Maryland : Paul H. Brookes Publishing Co., 1998)
Contains a collection of essays by education professionals that explain the educational benefits of cooperative learning the positive effects it has on social skills, and offers techniques for implementing cooperative learning strategies in any classroom environment.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Education;Education. -- Inclusive education;Mainstreaming in education;Special education;Children with disabilities;Multicultural education;Exceptional children -- United States.;United States.;United States.;United States.;United States; 20; 2